Psychological impact on health professionals in pandemic by COVID-19: Approach through the problematizing methodology (Research, Society and Development, 2021)
COVID-19 brought changes in the population's routine, as well as insecurity and fear of contamination. The aim of this study is to reflect on the need for psychological assistance to health professionals in the period of the pandemic by COVID-19 and to propose hypotheses for solutions. It is a socialization of results obtained from the use of the Problematizing Methodology (Arc Method), composed of five stages: observation of reality, key points, theorization, hypotheses of solution and application to reality. From the analysis of health services in Brazil, the mental health of health professionals in the period of the pandemic by COVID-19 was listed as a problem to be studied. Thus, a bibliographic review was carried out, using as inclusion criteria articles published between 2015 and 2020 on the topic. The search was carried out in the SciELO database in September 2020, using the descriptors "mental health assistance", "COVID-19", "worker health". From the observation of reality, the problem to be studied was listed and key points that contribute to the problem were defined. After justifying the need to expand the discussions, the hypotheses of solutions for solving the problem were listed. This study provided a discussion on ways to provide psychological assistance to professionals in the front line, capable of reducing psychological damage. The use of this methodology was beneficial to instigate critical discussion and search for solutions within the possibilities of the health service.